ISHLAH DALAM TAKHARUJ MENURUT HANAFIYAH VERSUS ISHLAH DALAM KOMPILASI HUKUM ISLAM (ANALISIS KEBIJAKAN HUKUM) - Elfia Elfia (Institut Agama Islam Negeri Batusangkar, 2018)
This study aims at analyzing the two forms of legal policy in the division of inheritance by using the principle of ishlah. The takharuj practices that develops in the Hanafi school allows the giving of inheritance rights to the heirs before the property is distributed (before the heirs dies) in the presence of the willingness of the other heirs. The term Ishlah is understood by giving rewards in exchange for the part of the resigned heirs. The principle of ishlah which permits the distribution of inheritance under the agreement of the heirs is also regulated in the Compilation of Islamic Law Article 183. But in that article, the existence of ishlah can be done after the heirs died (after the division of inheritance). This research is a library research by using normative law approach and analyzing the data by content analysis. As the findings from this study, there are several weak points in the completion of the takharuj so that clerics outside Hanafiyah school did not practice it. These weak points potentially violate the qath'i propositions and general principles in muamalah maaliyah. The peace (ishlah) in the Compilation of Islamic Law is easier to follow and does not violate the qath'i proofs in the Qur'an and Hadith.